Pengelolaan Pariwisata Berkelanjutan di Sekotong: Potensi dan Tantangan - Surayyal Hizmi; Ilham Junaid (Pusaka: Journal of Tourism, Hospitality, Travel and Business Event, 2023)
Sustainable tourism management is a crucial aspect that needs attention to improve the quality of destinations. Sekotong, an area in West Lombok regency, has a lot of potential that can be developed to support sustainable tourism, while studies on identifying the potential and implementing sustainable tourism in this area are still limited. This study aims to identify tourism potential in Sekotong as a tourism product and evaluate the implementation of sustainable tourism management in each destination of Sekotong. Data collection was carried out through the observation of four representative destinations, namely Mangrove Sekotong Tengah and Elak-Elak Beach representing marine tourism, Mareje Village for rural tourism, and 3 Gilis (Naggu, Tangkong, Sudak) representing island tourism. The research was conducted by observing the potencies of these destinations and then reviewing the implementation of the concept of sustainability. To obtain more information, researchers interviewed managers or tourism operators at each destination. The observation and interview referred to 4 pillars of the GSTC sustainable tourism standards. The results showed that there is a potential for cultural tourism products in Mareje village, marine and underwater tourism activities in 3 Gilis and Elak-Elak beach, as well as marine-based educational tours in Mangrove Sekotong Selatan. Referring to the 4 pillars in sustainable tourism, however, the management and provision of facilities need to be standardized and improved. In addition, several important strategies need to be implemented in improving the quality of these destinations such as synchronization among stakeholders and training in implementing destination management by considering all sustainable tourism concepts in accordance with the 4 pillars in the GSTC criteria.